Peutz-Jeghers syndrome a review of gynecological implications and the management of these patients through the presentation of a case report - Katarzyna Plagens-Rotman; Grażyna Jarząbek-Bielecka; Piotr Merks; Katarzyna Wróblewska-Seniuk; Małgorzata Mizgier; Ewa Jakubek; Samuel Grześkiewicz; Małgorzata Wójcik; Witold Kędzia (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: Peutz-Jeghers Syndrome (PJS) is a rare autosomal dominant genetic condition caused by mutations in STK11 (Serine/threonine kinase 11) gene (OMIM 602216 Serine/Threonine Protein Kinase 11) located in the short arm of chromosome 19 (19p.13.3). Case: We report the case of a 4 and ½ year-old female child with a rare Peutz-Jeghers Syndrome. She was admitted to the Clinic of Gynaecology, the Faculty of Perinatology and Gynaecology, Chair of Adolescence Gynaecology and Sexology at Poznan University of Medical Sciences, in order to undergo preventive medical examinations. The patient was accompanied by her mother. Age and sex-appropriate development. Age-appropriate dental condition. Gynaecological examination was conducted. No changes were identified through palpation. Normal ultrasound picture. No symptoms of genital mucosa estrogenization, which is typical of the patient’s age. A small amount of vaginal discharge was found. Pap smear was conducted to assess vaginal biocenosis. Lacidobacilli deficiency was found and feminine hygiene products, such as Iladian, were recommended. Melanotic macules around the mouth, typical of Peutz-Jeghers Syndrome were identified. Conclusions: Due to the increased cancer risk in patients with Peutz-Jeghers Syndrome, more frequent medical and gynaecological examinations are recommended for the girl. It should be noted that the girl’s mother decision to have her daughter examined at such a young age was appropriate.